TINJAUAN YURIDIS PERPRES NOMOR 64 TAHUN 2020 TENTANG PERUBAHAN KEDUA ATAS PERPRES NOMOR 82 TAHUN 2018 TENTANG JAMINAN KESEHATAN TERKAIT DENGAN PUTUSAN MAHKAMAH AGUNG NOMOR 7/P/HUM/2020 - Deri Nahrudin Syukri; Mexsasai Indra; Maria Maya Lestari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The issuance of Presidential Decree No. 64 of 2020 concerning HealthInsurance certainly raises question marks in the community. This regulationemerged after the Supreme Court's Decision on Presidential Regulation No. 75 of2020 which has the same substance, namely the increase in BPJS contributions.Presidential Regulation Number 64 of 2020 is considered to have violated theSupreme Court's decision and the laws above it. Therefore, the purpose of writingthisthesis is: first, why does the President continue to issue Presidential RegulationNo. 64 of 2020 concerning Increases in Health Insurance Contributions while theSupreme Court has decided Presidential Decree No. 75 of 2019 with Decision No.7/P/HUM/2020 which contains the same content. . Second, to find out the urgencyof the formation of Presidential Decree No. 64 of 2020.This research is a normative research. This is based on library researchthat takes quotes from reading books, or supporting books related to what theauthor isresearching. The data sourcesthat the researcher uses are secondary datasources consisting of primary, secondary ortertiary legal materials. This study usesqualitative data analysis and produces descriptive data.From the results of the research conducted, there are several conclusionsobtained, namely: First, in this case the President has the right to issue aPresidential Regulation. However, judging from the Supreme Court's decision aswell as the reasons for the rejection of the previous Presidential Regulation, it cancertainly be used as a reason why the President does not need to issue a newPresidential Regulation which basically contains the same content as the previousPresidential Decree. In addition, the President must pay attention to the impact andthe current state of society. Second, the reason for the President in issuing thisPresidential Regulation is in stark contrast to the principles of the social securitysystem, which in the hierarchy should not conflict with the regulations above.Keywords: Presidential Regulation-Health Insurance-Supreme Court Decision